Pandangan Yusuf Al-Qardhawi Tentang Sikap Umat Islam Terhadap Sunnah Tasyri’iyyah - Prabowo, Heri Bayu Dwi; Jamilah, Eva Syarifatul (Islamadina : Jurnal Pemikiran Islam, 2022)
The Jargon back to al-qur’an and sunnah (ar-ruju’ ila al-qur’an wa sunnah) is being fough massively by many groups. Supported through social media, the dissemination of religious teachings under the guise of a need for some groups, is framed in such a way that it creates a distinct caos in the level of religious community life. Understanding of these two terms must be accompanied by an open attitude and mutual understanding of differences as a result of interpretation of them. Referring to existing problematics, the researcher tries to describe it through a post-positivism approach with a focus on the discourse of a well-known Muslim figure named Yusuf al-Qardhawi, through his work entitled as-sunnatu Masdharan lil Ma’rifati wal Hadharati (sunnah Rasul: the source of knowledge and civilization). As a result, studying.sunnah must be done carefully, by distinguishing between sunnah with legal dimension (tasyri’iyyah) and sunnah that has no legal dimension (ghairu tasyri’iyyah), referring to the principles and methods of understanding the sunnah that have been established by ulama. As a form of predence in the understanding of Muslims towards the sunnah, it is necessary to base oneself on the resultt of the ijtihad of ulama, especially lay people and who are just getting acquainted with the sunnah.